Antioxidant Activity of Polar Fraction of Methanol Extract from Tree Bark Of Shorea acuminatissima with DPPH Method - Haryoto Haryoto; Broto Santoso; Hafid Nugroho (Jurnal ILMU DASAR, 2007)
Shorea accuminatissima, which is known locally as Meranti kuning, is one species of Dipterocarpaceae family. This plant contains compounds that are expected to have antioxidant activity. This research was carried out to examine the radical scavenger activity of polar fraction of methanolic extract from the tree bark of S. accuminatissima by using DPPH (2,2-difenil- 1-pikrilhidrazil) method with vitamin C as comparator. Powder of tree bark of S. accuminatissima was macerated in methanol. The methanolic extract was then evaporated to obtained dry extract. Extract with concentration of 200, 100, 50, 25 and 10 µg/mL were used to test its radical scavenger activity. The result showed that polar fraction of methanolic extract and vitamin has IC value of 319.83 and 3.72 µg/mL, respectively.